Mental Health Literacy, Stigma, and Help-Seeking Behavior: A Study Among Teenagers in Rumuolumeni, Rivers State - Aisiku, Osebhahiemen Andrea; Imarenezor, Edobor Peter Kenneth (African Journal of Medicine, Surgery and Public Health Research, 2025)
Adolescence is a critical period of significant physical, emotional, and social change, during which mental health problems often emerge. In Nigeria, the prevalence of mental health issues among adolescents is a growing concern, with studies suggesting that up to 20% of adolescents experience mental health problems. However, mental health literacy (MHL), which refers to the knowledge and beliefs about mental health and mental illness, is often poor among adolescents, leading to delayed or inadequate help-seeking. Furthermore, stigma and discrimination against individuals with mental illness are pervasive in Nigerian society, creating a significant barrier to help-seeking behaviour (HSB). In Rivers State, Nigeria, where this study is situated, there is a paucity of research on mental health literacy, stigma, and help-seeking behaviour among adolescents. This study aims to address this knowledge gap by investigating the level of mental health literacy, the impact of stigma, and help-seeking behaviours among teenagers in Rumuolumeni, Rivers State. A cross-sectional survey was conducted among 285 secondary school students (ages 13-19) from public and private schools. Data were collected using structured questionnaires and vignettes assessing knowledge of mental health conditions, attitudes toward stigma, and preferred help-seeking pathways. Chi-square tests were used to analyse associations between demographic factors and key mental health variables. The results show that 56.9% of participants could recognize symptoms of mental health conditions in themselves. However, fewer students accurately identified depression (36.3%), anxiety (22.8%), and addiction (41%). Stigma was a major barrier, with 24.8% of respondents reporting personal experiences of discrimination, often from friends (55.9%) and family (30.9%). Help-seeking was predominantly informal, with 64.9% preferring parents/guardians over mental health professionals (13.6%). While gender, age, and school type showed no significant associations with MHL, stigma, or HSB, religion significantly influenced stigma (p = 0.020). These findings emphasize the need for urgent attention to promote mental health literacy, reduce stigma, and encourage help-seeking behaviour among teenagers in Rumuolumeni, Rivers State. The findings suggest that adolescent-centred mental health education, stigma-reduction campaigns, and community-based interventions are essential to promote early intervention and improve adolescent mental health outcomes. By strengthening school curricula, training parents and guardians, and engaging religious leaders and the community, we can work towards creating a supportive environment that encourages teenagers to seek help and promotes positive mental health outcomes. The study's findings have important implications for policymakers, educators, healthcare providers, and community leaders working to promote adolescent mental health in Nigeria.